Nonsurgical periodontal treatment during pregnancy and rates of preterm birthAJOG Global Reports at a Glance - Gregory C. Valentine, MD, MEd, FAAP; Krystle Perez, MD, MPH; Adino T. Tsegaye, MPH; Daniel A. Enquobahrie, MD, MPH, PhD; David Couper, PhD; James D. Beck, MS, PhD; Rachel Umoren, MBBCh, MS; Kjersti M. Aagaard, MD, PhD; Christy M. McKinney, PhD (Elsevier, 2023)
BACKGROUND: Periodontitis during pregnancy is associated with an increased risk of preterm birth (<37 weeks of gestation) or low birthweight (<2500 g) offspring. Beyond periodontal disease, the risk of preterm birth varies both by previous history of preterm birth and in association with social determinants prevalent among vulnerable and marginalized populations. This study hypothesized that the timing of periodontal treatment during pregnancy and/or social vulnerability measures modified the response to dental scaling and root planing for the treatment of periodontitis and prevention of preterm birth. OBJECTIVE: This study aimed to determine the association of timing of dental scaling and root planing for gravidae with a diagnosed periodontal disease on the rates of preterm birth or low birthweight offspring among subgroups or strata of gravidae as part of the Maternal Oral Therapy to Reduce Obstetric Risk randomized controlled trial. All participants in the study had clinically diagnosed periodontal disease and differed by the timing of the periodontal treatment (dental scaling and root planing at <24 weeks [per protocol] or after delivery) or by baseline characteristics. Although all participants met the well-accepted clinical criteria for periodontitis, not all participants acknowledged a priori that they had periodontal disease. STUDY DESIGN: This was a per-protocol analysis of data from 1455 participants of the Maternal Oral Therapy to Reduce Obstetric Risk trial evaluating dental scaling and root planing on the risk of preterm birth or low birthweight offspring. Adjusted multiple logistic regression to control for confounders was used to estimate associations comparing the timing of periodontal treatment in pregnancy to receiving treatment after pregnancy (referent control) on rates of preterm birth or low birthweight among subgroups of gravidae with known periodontal disease. Study analyses were stratified, and the associations with the following characteristics-body mass index, self-described race and ethnicity, household income, maternal education, recency of immigration, and self-acknowledgment of poor oral health, were explored. RESULTS: Dental scaling and root planing during the second or third trimester of pregnancy were associated with an increased adjusted odds ratio of preterm birth among those at the lower body mass index strata (18.5 to <25.0 kg/m2) (adjusted odds ratio, 2.21; 95% confidence interval, 1.07-4.98), but not among individuals who were overweight (body mass index of 25.0 to <30.0 kg/m2; adjusted odds ratio, 0.68; 95% confidence interval, 0.29-1.59) or obese (body mass index of ≥30 kg/m2; adjusted odds ratio, 1.26; 95% confidence interval, 0.65-2.49). There was no significant difference in pregnancy outcomes related to the other evaluated variables: self-described race and ethnicity, household income, maternal education, immigration status, or self-acknowledgment of poor oral health. CONCLUSION: In this per-protocol analysis of the Maternal Oral Therapy to Reduce Obstetric Risk trial, dental scaling and root planing had no preventive benefit against adverse obstetrical outcomes and were associated with increased odds of preterm birth among individuals at lower body mass index strata. There was no significant difference in the occurrence of preterm birth or low birthweight after dental scaling and root planing periodontitis treatment concerning other analyzed social determinants of preterm birth.